2010
DOI: 10.1186/1471-2393-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Using targeted vouchers and health equity funds to improve access to skilled birth attendants for poor women: a case study in three rural health districts in Cambodia

Abstract: BackgroundIn many developing countries, the maternal mortality ratio remains high with huge poor-rich inequalities. Programmes aimed at improving maternal health and preventing maternal mortality often fail to reach poor women. Vouchers in health and Health Equity Funds (HEFs) constitute a financial mechanism to improve access to priority health services for the poor. We assess their effectiveness in improving access to skilled birth attendants for poor women in three rural health districts in Cambodia and dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
241
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(268 citation statements)
references
References 23 publications
18
241
0
9
Order By: Relevance
“…This observation was true even for universal schemes, which suggests that mainly the poorest women were encouraged by vouchers to give birth in a public facility, perhaps because of a perception that the quality of care is lower and staff attitudes are worse than in private facilities. 13 Targeting may, therefore, increase the administrative costs of a voucher scheme without having an effect on how different population groups benefit from the vouchers.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was true even for universal schemes, which suggests that mainly the poorest women were encouraged by vouchers to give birth in a public facility, perhaps because of a perception that the quality of care is lower and staff attitudes are worse than in private facilities. 13 Targeting may, therefore, increase the administrative costs of a voucher scheme without having an effect on how different population groups benefit from the vouchers.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of demand and supply side incentives, as seen in Nicaragua, has improved utilization of preventive services among the poor and our study favors a combined approach (28). In remote rural settings measures are needed at facilitating transport access and a number of measures have been identified including community revolving funds for transport, transporter-community links facilitated by NGOs, and transport vouchers (29)(30)(31). BCC has proved to be effective for birth preparedness and newborn care (32), and in this case calls for inclusion of husbands and inlaws.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,[43][44][45] Several initiatives have been launched since the 1980s to address these barriers faced by poor and rural women in low-and middle-income countries, such as increased access to institutional deliveries for poor women, home delivery by skilled attendants, training of traditional birth attendants, and vouchers for delivery in a health facility, among others. [46][47][48][49] Although some of these initiatives were successful at local or national level, they were not sufficiently scaled up to have an impact at global level. An analysis of 75 countries with high maternal and child mortality showed that coverage with skilled birth attendance increased by less than 1 percentage point a year from 41% in 1990 to 65% in 2015.…”
Section: Discussionmentioning
confidence: 99%